Evolution of the Northeastern Arabian Plate Margin and Shelf: Hydrocarbon Habitat and Conceptual Future Potential L'évolution géologique de la plate-forme arabe et de sa marge : répartition des hydrocarbures et concepts pour son potentiel futur - Beydoun Z. R. (Oil & Gas Science and Technology, 2006)
About 98% of the huge recoverable hydrocarbon reserves of the Arabian Plate are concentrated in the Northeastern Margin Shelf extending from NW Iraq through the Gulf to Central Oman. The plate tectonic evolution of this region is reviewed as background for its enormous hydrocarbon productivity. This is intimately linked to a near-continuous passive margin history and gentle subsidence of an extraordinarily wide epeiric shelf, which allowed repeated regional development of source rocks in large intra-shelf basins frequently in optimal juxtapositional relationships with good regional reservoirs and seals; these events are discussed. Although currently reported reserve figures relate to Mesozoic and Tertiary reservoirs, it is concluded that several pre-Mesozoic regional sources have generated enormous volumes of hydrocarbons, the bulk of which still await discovery in up-dip Paleozoic reservoirs, and that future ultimate recoverable reserves could conceivably double. Près de 98 % des énormes réserves récupérables d'hydrocarbures de la plaque arabique sont concentrés dans la marge nord-est qui s'étend du nord-ouest de l'Irak au centre d'Oman, à travers le Golfe. L'auteur passe en revue l'évolution tectonique de cette région, origine de son énorme productivité pétrolière. La passivité presque continue de cette marge, combinée à l'affaissement progressif d'un plateau épicontinental particulièrement large, a permis le développement local répété de roches mères, au sein du plateau, dans de vastes bassins bénéficiant souvent d'une juxtaposition optimale avec les roches réservoir et roche-couvertures. L'article étudie ces évènements. Si les réserves actuellement prises en compte sont essentiellement d'origine mésozoïque et tertiaire, l'auteur conclut que de nombreuses sources régionales pré-mésozoïques ont généré d'énormes volumes d'hydrocarbures, dont la majeur partie reste à découvrir dans des réservoirs paléozoïques situés en amont, ce qui pourrait conduire à doubler le volume des réserves récupérables dans l'avenir.